SummonBrush Enhancing Touch Interaction on Large XR User Interfaces by Augmenting Users' Hands with Virtual Brushes - Tian, Yang (IEEE transactions on visualization and computer graphics, 2025)
Touch interaction is one of the fundamental interaction paradigms in XR, as users have become very familiar with touch interactions on physical touchscreens. However, users typically need to perform extensive arm movements for engaging with XR user interfaces much larger than mobile device touchscreens. We propose the SummonBrush technique to facilitate easy access to hidden windows while interacting with large XR user interfaces, requiring minimal arm movements. The SummonBrush technique adds a virtual brush to the index fingertip of a user's hand. Upon making contact with a virtual user interface, the brush bends and diverges and ink starts to diffuse in it. The more the brush bends and diverges, the more the ink diffuses. The user can summon hidden windows or background applications in situ, which is achieved by firstly pressing the brush against the user interface to make ink fully fill the brush and then perform swipe gestures. Also, the user can press the brush against the thumbtails of background applications in situ to quickly cycle them through. Ecological studies showed that SummonBrush significantly reduced the arm movement time by 39% and 34% in summoning hidden windows and activating/closing background applications, respectively, leading to a significant decrease in reported physical demand